The Impact of the Follow-Up Process on Improving Training Outputs: A Case Study of the Education Department in Al Ahsa Region (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to emphasize the importance of applying the follow-up process after the completion of training programs on improving the training outputs. This study was, mainly, designed on quantitative and qualitative approaches using a case study strategy to accomplish its objectives and to answer its questions. This case study was applied to the Human Resource Development Unit's female section at the Education Department in AlAhsa region (HRDUF). The quantitative approach of this study was based, mainly, on questionnaire developed by the researcher of this study which was distributed to some targeted groups of trainees. The developed questionnaire comprises three main sections, namely, basic data about trainee, questions about training programs, and questions about the impact of training follow-up process. On the other hand, the qualitative approach focused on interviewing a number of trainers at the HRDUF with specific questions, among which, their experiences in providing training programs, their views about the importance of follow-up process, their readiness to implement follow-up process, and Pros and Cons of follow-up process. The results confirmed the validity of the study hypotheses and compatibility with the study questions about the importance of: a) applying the training follow-up process to enhance knowledge, skills, and attitude (KSA) of trainees and to promote high productivity at the workplace, and b) incorporating follow-up process in the future training programs.
Keywords: Training Outputs; the Follow-Up Process; the Education Department in Al Ahsa Region; KSA